Neonatal lesions of orbital frontal areas 11/13 in monkeys alter goal-directed behavior but spare fear conditioning and safety signal learning - Kazama, Andy M.; Davis, Michael; Bachevalier, Jocelyne (Frontiers in Neuroscience, 2014)
Recent studies in monkeys have demonstrated that damage to the lateral subfields of orbital frontal cortex (OFC areas 11/13) yields profound changes in flexible modulation of goal-directed behaviors and a lack in fear regulation. Yet, little consideration has been placed on its role in emotional and social development throughout life. The current study investigated the effects of neonatal lesions of the OFC on the flexible modulation of goal-directed behaviors and fear responses in monkeys. Infant monkeys received neonatal lesions of OFC areas 11/13 or sham-lesions during the first post-natal week. Modulation of goal-directed behaviors was measured with a devaluation task at 3-4 years and 6-7 years. Modulation of fear reactivity by safety signals was assessed with the AX+/BX- potentiated-startle paradigm at 6-7 years. Similar to adult-onset OFC lesions, selective neonatal lesions of OFC areas 11/13 yielded a failure to modulate behavioral responses guided by changes in reward value, but spared the ability to modulate fear responses in the presence of safety signals. These results suggest that these areas play a critical role in the development of behavioral adaptation during goal-directed behaviors, but not, or less so, in the development of the ability to process emotionally salient stimuli and to modulate emotional reactivity using environmental contexts, which could be supported by other OFC subfields, such as the most ventromedial subfields (i.e. areas 14/25). Given similar impaired decision-making abilities and spared modulation of fear followed both neonatal lesions of either OFC areas 11 and 13 or amygdala (Kazama et al., 2012; Kazama & Bachevalier, 2013), the present results suggest that interactions between these two neural structures play a critical role in the development of behavioral adaptation; an ability essential for the self-regulation of emotion and behavior that assures the maintenance of successful social relationships.